Benign-Metal-Catalyzed Carbon–Carbon and Carbon–Heteroatom Bond Formation - Ranu, Brindaban C.; Adak, Laksmikanta; Mukherjee, Nirmalya; Ghosh, Tubai (Synlett, 2022)
Carbon–carbon and carbon–heteroatom bond-formation reactions catalyzed by benign and inexpensive metals are of much interest in organic synthesis, as these reactions provide green and cost-effective routes. This account summarizes our recent contributions to the construction of carbon–carbon and carbon–heteroatom bonds by using benign-metal catalysts. A number of carbon–heteroatom bond formations, including C–N, C–O, C–S, C–Se, C–Te, and C–P bond formations, are discussed. Mechanistic insights into several reactions are also reported1 Introduction2 C–C Bond Formation3 C–N and C–O Bond Formation4 Carbon–Chalcogen (C–S, C–Se, C–Te) and C–P Bond Formation5 Conclusions
Keywords: catalysis; benign metals; carbon–carbon bond formation; carbon–heteroatom bond formation; cross-coupling; green chemistry